2009
DOI: 10.1111/j.1463-1318.2008.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency surgery for complicated acute diverticulitis

Abstract: Aim Antecedent attacks of diverticulitis are thought to increase the risk of complicated diverticulitis, and unless elective surgery is performed, a high proportion of patients with recurrent symptoms will require emergency operations for complicated diverticulitis with its associated morbidity. In this multicentre study, we aim to assess impact of previous attacks of diverticulitis on patients requiring an emergency surgical intervention.Method All patients operated on as an emergency for complicated divertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
15
0
6
Order By: Relevance
“…Issa et al 31 in their study on emergency surgery for complicated diverticulitis report a mortality of 13.5% including patients of all ages. Arenal and Bengoechea-Beeby 2 report a mortality of 22% in their work on emergency abdominal surgery in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Issa et al 31 in their study on emergency surgery for complicated diverticulitis report a mortality of 13.5% including patients of all ages. Arenal and Bengoechea-Beeby 2 report a mortality of 22% in their work on emergency abdominal surgery in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…20 This thesis is underlined by several other studies, which have shown that complicated diverticulitis most commonly occurred during the first episode rather than during recurrent episodes. [21][22][23] Therefore, the aim in IS patients is to avoid diverticulitis. Smoking and obesity are known to increase the incidence of diverticulitis and complicated diverticulitis [24][25][26][27] ; in contrast physical activity prevents diverticulitis and reduces the risk of complicated diverticulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Częstość zachorowania zwiększa się tam wraz z wiekiem. Wśród osób w wieku 40 lat uchyłkowatość wystę-puje u mniej niż 10%, natomiast w wieku 80 lat u 50-66% [6,8,9]. U większości pacjentów uchyłkowatość przebiega bezobjawowo, a tylko u 15-20% pojawiają się cechy ostrego stanu zapalnego.…”
Section: Epidemiologiaunclassified
“…Głównym celem postępowania terapeutycznego w zapaleniu otrzewnej jest ustalenie przyczyny oraz jak najszybsze rozpoczęcie kierunkowego leczenia, tak aby uchronić pacjenta przed wystąpieniem groźnych powikłań: wstrząsu, sepsy i MOF [5,8,13,28,37]. Zapalenie otrzewnej jest w większości przypadków następstwem choroby narządów leżących w jamie brzusznej.…”
Section: Leczenie Zasadniczeunclassified
See 1 more Smart Citation